Peran Metode Fraksinasi dalam Pemurnian Protein dan Enzim - Nita Magfirah Ilyas (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Fractionation is a method for separating proteins and enzymes widely used in biochemistry. Enzyme precipitation can be performed using either organic solvents or salts. This method is useful for separating protein components in crude enzyme extracts from non-protein components. The most commonly used salt is ammonium sulfate because it has high solubility, is relatively stable, and can precipitate proteins without causing denaturation. Commonly used organic solvents are n-hexane, ethyl acetate, water, ethanol, and methanol. This literature review aims to analyze the application of fractionation methods with salts and solvents in protein and enzyme purification based on reviewed articles. The method used is a literature review by examining research results from several articles related to extraction, fractionation, compound content analysis, and specific activity tests. The review results show that salt fractionation is effective in increasing the purity and concentration of proteins or enzymes. Several studies have shown that ammonium sulfate saturations of 20–40%, 50%, and 60% often produce the highest enzyme specific activity or protein content. The review results show that the ethyl acetate solvent fraction often provides the highest specific activity due to its ability to attract semipolar compounds such as flavonoids, phenols, certain alkaloids, and other active secondary metabolites. However, precipitation using salt is superior and advantageous compared to organic solvents. Therefore, salt fractionation is a simple, inexpensive, and effective method for the initial stage of protein and enzyme purification before proceeding with dialysis, chromatography, or further characterization.